2017
DOI: 10.1080/1359432x.2017.1308924
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mindfulness on well-being and performance in the workplace: an inclusive systematic review of the empirical literature

Abstract: Work can be demanding, imposing challenges that can be detrimental to the physical and mental health of workers. Efforts are therefore underway to develop practices and initiatives that may improve occupational wellbeing. These include interventions based on mindfulness meditation. This paper offers a systematic review of empirical studies featuring analyses of mindfulness in occupational contexts. Databases were reviewed from the start of records to January 2016. Eligibility criteria included experimental and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
185
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(198 citation statements)
references
References 135 publications
11
185
1
1
Order By: Relevance
“…Numerous reviews of mindfulness and meditation studies have been conducted to assess their impact on physical and mental health across general populations, on clinical and medical samples, and in students (e.g., Chiesa & Serretti, ; Grossman et al, ; Khoury et al, ; Khoury, Sharma, Rush, & Fournier, ). Similar growth has occurred in organizational applications in both mixed‐employee samples (e.g., Lomas, Medina, Ivtzan, Rupprecht, & Eiroa&Orosa, ; Virgili, ) and within specific occupational industries, including health care (e.g., Burton, Burgess, Dean, Koutsopoulou, & Hugh‐Jones, ; Lomas, Medina, Ivtzan, Rupprecht, & Eiroa‐Orosa, , ; Luken & Sammons, ; Smith, ) and education (e.g., Hwang, Bartlett, Greben, & Hand, ; Klingbeil & Renshaw, ; Lomas, Medina, Ivtzan, Rupprecht, & Eiroa‐Orosa, ).…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Numerous reviews of mindfulness and meditation studies have been conducted to assess their impact on physical and mental health across general populations, on clinical and medical samples, and in students (e.g., Chiesa & Serretti, ; Grossman et al, ; Khoury et al, ; Khoury, Sharma, Rush, & Fournier, ). Similar growth has occurred in organizational applications in both mixed‐employee samples (e.g., Lomas, Medina, Ivtzan, Rupprecht, & Eiroa&Orosa, ; Virgili, ) and within specific occupational industries, including health care (e.g., Burton, Burgess, Dean, Koutsopoulou, & Hugh‐Jones, ; Lomas, Medina, Ivtzan, Rupprecht, & Eiroa‐Orosa, , ; Luken & Sammons, ; Smith, ) and education (e.g., Hwang, Bartlett, Greben, & Hand, ; Klingbeil & Renshaw, ; Lomas, Medina, Ivtzan, Rupprecht, & Eiroa‐Orosa, ).…”
Section: Introductionmentioning
confidence: 77%
“…Still, reviews have identified several important issues that warrant further attention, several of which we address in the present study. First, reviews suggest a lack of methodological rigour (see Eby et al, in press; Jamieson & Tuckey, ; Janssen et al, ; Lomas et al, ). Common issues include inattention to intervention fidelity, poorly controlled studies lacking in internal and external validity, absent manipulation checks, and inadequate reporting.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations